2021
DOI: 10.3126/kumj.v19i3.49715
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression and Functional Impairment among Health Care Workers during COVID-19 Pandemic: A Crosssectional Online Survey

Abstract: Background COVID-19 is an infectious disease caused by a newly discovered coronavirus. The number of cases and dramatic loss of human life worldwide created psychological problems among general public, including health care workers. Objective To determine the burden of anxiety, depression, and functional impairment among health care workers in the early days of lockdown during the first wave of COVID-19 outbreak in Nepal. Method A hospital-based cross-sectional study was carried out among all the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
4
2
0
Order By: Relevance
“…Heightened endorsement moral distress and symptoms of depression, anxiety, stress and PTSD were significantly associated with a higher level of functional impairment among RTs in the present study. The present findings are consistent with an investigation of hospital-based HCPs in Nepal, where depression and anxiety scores correlated positively with functional impairment (Shrestha et al, 2021 ) along with reports of an association between negative psychological impacts and insomnia among HCPs during the pandemic (Lai et al, 2020 ; Pappa et al, 2020 ). Overall, the present characterization of psychological and functional profiles among Canadian RTs appear consistent with reports from other HCPs during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Heightened endorsement moral distress and symptoms of depression, anxiety, stress and PTSD were significantly associated with a higher level of functional impairment among RTs in the present study. The present findings are consistent with an investigation of hospital-based HCPs in Nepal, where depression and anxiety scores correlated positively with functional impairment (Shrestha et al, 2021 ) along with reports of an association between negative psychological impacts and insomnia among HCPs during the pandemic (Lai et al, 2020 ; Pappa et al, 2020 ). Overall, the present characterization of psychological and functional profiles among Canadian RTs appear consistent with reports from other HCPs during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Another study examining anxiety, depression and functioning in healthcare workers (clinical and non-clinical employees) reported that the mean of their total functioning scores was 19.47, which falls closer to the 92.4th percentile. 37 This study indicates similar levels of disability/functioning as our current sample.…”
Section: Discussionsupporting
confidence: 77%
“…A study by Shrestha et al 37 had similar findings for their overall WHODAS V.2.0 functioning score. They found that anxiety and depression in healthcare workers led to a low impairment in functioning during the COVID-19 pandemic 37…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations